2004
DOI: 10.1105/tpc.103.018648
|View full text |Cite
|
Sign up to set email alerts
|

The xipotl Mutant of Arabidopsis Reveals a Critical Role for Phospholipid Metabolism in Root System Development and Epidermal Cell Integrity

Abstract: Phosphocholine (PCho) is an essential metabolite for plant development because it is the precursor for the biosynthesis of phosphatidylcholine, which is the major lipid component in plant cell membranes. The main step in PCho biosynthesis in Arabidopsis thaliana is the triple, sequential N-methylation of phosphoethanolamine, catalyzed by S-adenosyl-l-methionine:phosphoethanolamine N-methyltransferase (PEAMT). In screenings performed to isolate Arabidopsis mutants with altered root system architecture, a T-DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
130
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 57 publications
5
130
0
1
Order By: Relevance
“…This organic phosphate ester might serve for phosphate and nitrogen storage and is distributed by the vascular system throughout the plant 14,15 . The idea that choline can be taken up from the media and distributed within the plant is further supported by the observation that externally supplied choline can rescue the developmental defects of xipotl, a phosphocholine biosynthesis mutant 16 . Choline might also be transported by the proline transporter BvBet/ProT1, which is expressed in phloem and xylem parenchyma cells of sugar beet 17 .…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This organic phosphate ester might serve for phosphate and nitrogen storage and is distributed by the vascular system throughout the plant 14,15 . The idea that choline can be taken up from the media and distributed within the plant is further supported by the observation that externally supplied choline can rescue the developmental defects of xipotl, a phosphocholine biosynthesis mutant 16 . Choline might also be transported by the proline transporter BvBet/ProT1, which is expressed in phloem and xylem parenchyma cells of sugar beet 17 .…”
mentioning
confidence: 68%
“…2d), indicating that CHER1 may be involved in the regulation and/or maintenance of choline metabolite levels in plants. Furthermore, we analysed the expression of pAPL::GFPer and the distribution of the freely moving GFP driven by the phloem CC-specific pSUC2 promoter during phloem development in the biosynthetic xipotl mutant, which also shows reduced levels of choline and phosphocholine 16,37 . Similar to cher1-1, we observed a reduced movement and unloading defects of pSUC2::GFP ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PCho has been shown to affect the expression of XIPOTL1 indirectly, through the action of an upstream regulatory mORF (Alatorre- Cobos et al, 2012). Previous studies have reported altered root architecture and epidermal cell death in a XIPOTL1/PEAMT1 KO mutant (xpl1; Cruz-Ramírez et al, 2004). However, even though PCho content was effectively diminished in this mutant, the described phenotype was more likely caused by an impaired balance of choline, PtdCho, and phosphatidic acid (Cruz-Ramírez et al, 2004;AlatorreCobos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Results from our work and others indicate that altered PtdCho and choline contents are responsible for these phenotypes, rather than PCho or PEth, since specifically affecting their concentrations did not influence root architecture. For instance, XIPOTL1 converts PEth to PCho through a triple methylation and is strongly involved in the PtdCho balance in membranes (McNeil et al, 2001;Cruz-Ramírez et al, 2004). Furthermore, PCho has been shown to affect the expression of XIPOTL1 indirectly, through the action of an upstream regulatory mORF (Alatorre- Cobos et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation